THE RELATIONSHIP BETWEEN BASIC CULTURAL SCIENCES (IBD) AND CULTURAL ENGINEERING ON CAMPUS IN ACHIEVING STUDENT LEARNING OUTCOMES AT STKIP AHLUSSUNNAH BUKITTINGGI CAMPUS - Istiqlal, Abdul (Jurnal Ilmu Pendidikan Ahlussunnah, 2023)
At this time the values of religion, morals, humanity, and cultural values are in decline. Especially in college. Many students on campus experienced degradation of religious values, morals, humanity, and other cultural values. This has an influence on the learning outcomes of students, especially in the subject of basic cultural studies (IBD). This affects the attitude and behavior of students with a form of culture that is reflected, both on campus and in the community. This study tries to see the relationship between the provision of basic Buddhist science matakulia with cultural engineering on campus in the achievement of student learning outcomes on campus Stkip Ahlussunnah. The method and type of this research is qualitative resesach, which uses informants, lecturers, students, and achievement of learning outcomes. In this study, the author limits the problem to the relationship of basic cultural studies (IBD) with cultural engineering on campus in the achievement of student learning outcomes on campus Ahlussunnah Bukittinggi. The results of this study indicate that the provision of this basic Crocodile science (IBD) course affects a significant relationship to the learning outcomes of students in higher education. This has a positive impact on the progress of education in Indonesia at this time.